2021
DOI: 10.3389/fgene.2021.728563
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Genes and Loci Associated With Bone Mineral Density Based on Mendelian Randomization

Abstract: Bone mineral density (BMD) is a complex and highly hereditary trait that can lead to osteoporotic fractures. It is estimated that BMD is mainly affected by genetic factors (about 85%). BMD has been reported to be associated with both common and rare variants, and numerous loci related to BMD have been identified by genome-wide association studies (GWAS). We systematically integrated expression quantitative trait loci (eQTL) data with GWAS summary statistical data. We mainly focused on the loci, which can affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These findings of osteoporosis as a potential sex-specific predictor of AD, with shared relationships through MS4A6A , is an unknown and unexpected result identified from single-hypothesis-driven follow-up from our prediction models. Prior studies have established the MS4A gene cluster as a risk for AD, with one study identifying the cluster based on Mendelian randomization 77 , and another that identified a stronger female-specific effect size for MS4A6A 78 . Some studies investigating the role of the MS4A family suggest mechanisms that involve immune function, particularly among microglia 79 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings of osteoporosis as a potential sex-specific predictor of AD, with shared relationships through MS4A6A , is an unknown and unexpected result identified from single-hypothesis-driven follow-up from our prediction models. Prior studies have established the MS4A gene cluster as a risk for AD, with one study identifying the cluster based on Mendelian randomization 77 , and another that identified a stronger female-specific effect size for MS4A6A 78 . Some studies investigating the role of the MS4A family suggest mechanisms that involve immune function, particularly among microglia 79 .…”
Section: Discussionmentioning
confidence: 99%
“…A bone mineral density GWAS analysis of female patients shows p-value association with AD GWAS around the MS4A family locus, and this is further supported by MS4A6A eQTL colocalization with both Alzheimer and female HBMD. Prior studies have established the MS4A gene cluster as a risk for AD, with one study identifying the cluster based on mendelian randomization 60 , and another that identifies a stronger female-specific effect size for MS4A6A 61 . Some studies investigating the role of the MS4A family suggest mechanisms that involve immune function, particularly among microglia 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis demonstrates the complex function of candidate genes and reinforces the need for functional studies to clarify causality. More recently, summary data-based Mendelian randomization (SMR) analysis was implemented to investigate new genes and loci associated with BMD [ 18 ]. SMR performs an aggregation of the GWAS SNPs with data from expression quantitative trait loci (eQTL).…”
Section: Large Gwas and Wgs Have Identified Multiple Loci Associated ...mentioning
confidence: 99%
“…SMR performs an aggregation of the GWAS SNPs with data from expression quantitative trait loci (eQTL). The authors identified 12,477 SNPs that regulated 564 genes, which are associated with BMD [ 18 ]. Still, the function for many of these genes is unknown, especially whether it is relevant to bone homeostasis.…”
Section: Large Gwas and Wgs Have Identified Multiple Loci Associated ...mentioning
confidence: 99%